Advances in the Rapid Detection of Foodborne Pathogens by Nucleic Acid Amplification Lateral Flow Assays - Ziguang YUN; Yong WEI; Jian ZHANG; Shuangshuang CUI; Can LI; Fengxia SUN (Shipin gongye ke-ji, 2024)
Foodborne pathogens remain a serious threat to food safety, while traditional assays are time-consuming and labor-intensive, and difficult to match with the rapid and simple requirements of modern food safety detection. Molecular biology-based assays, such as polymerase chain reaction, isothermal nucleic acid amplification, and clustered regularly interspaced short palindromic repeats-based nucleic acid detection technology, have been widely employed in the detection of foodborne pathogens, and play an important role in ensuring food safety. In recent years, the combination of nucleic acid amplification detection technology and immunochromatography technology has become a hotspot for rapidly detecting foodborne pathogens. Here, the research progress in the rapid detection of foodborne pathogens are summarized by combining nucleic acid amplification and lateral flow immunoassays, highlight their advantages and disadvantages, and provide a comprehensive outlook on this field. This review can provide a reference for detecting, preventing, and controlling foodborne pathogens.